"Bound Over to Satan's Tyranny": Sin and Satan in Contemporary Reformed Hamartiology. Issue 1 (April 2018) - Ziegler, Philip G.
What might be the shape of a Reformed account of sin that does justice to the soteriological necessity of conceiving of salvation as a "three agent drama" involving God, the human, and those powers inimical to God of which the Devil is a synecdoche? What role ought the figure of Satan play in contemporary hamartiology, and what is at stake in asking and answering such a question? In conversation with recent work in Pauline apocalyptic as well as the work of G.C. Berkouwer as a developed example of the treatment of Satan in modern Protestant soteriology, this article explores these questions with a view to discerning possibilities for constructive restatement.